Mort Du Docteur J. Julio Henna - Todd, Roberto H.; Henna, J. J. (My University, 1924)
Mort du docteur J. Julio Henna. La colonie francaise de New York perd en lui un de ses plus fidéles amis
Keywords: Henna, José Julio, 1848-1924